Taiping North Road Footbridge—Innovative Folding Girder and Cable Support System. Issue 4 (2nd October 2018) - Yuan, Aimin; Xu, Donghui; Li, Bingnan; Liu, Jun
Abstract: To eliminate safety hazards and improve the traffic flow resulting from heavy vehicular and pedestrian traffic due to the demolition of a footbridge, a replacement footbridge was designed that uses lightweight folding girders, a multi-mast cable support system and multiple pylons. This new footbridge is regarded as an elegant solution due to its commendable constructability, sufficient design redundancy and cost competiveness. A finite-element method (FEM) model was established to determine the static and dynamic characteristics of the new footbridge. The natural frequencies and corresponding mode shapes of the footbridge were obtained, and comfort levels were evaluated according to the EN03 specification.